Immunofluorescence visualization of germ-line-specific cytoplasmic granules in embryos, larvae, and adults of Caenorhabditis elegans. - Strome, S (1982)
By using fluorescent antibody staining, we have followed cytoplasmic granules unique to germ-line cells throughout the life cycle of Caenorhabditis elegans. These elements, designated P granules, are segregated exclusively to germ-line precursor cells during early embryogenesis. Prior to mitosis at each of the early cleavages that produce a somatic and germ-line daughter cell, the granules become localized in the region of cytoplasm destined for the germ-line daughter. After the 16-cell stage, the granules appear to be associated with the nuclear envelope. P granules persist in the germ cells throughout the larval and adult stages. The P granules are similar in number, size, and distribution to germ-line-specific structures identified as "germinal plasm" by electron microscopy in C. elegans embryos.